REDESAIN TEBAL PERKERASAN JALAN LENTUR MENGGUNAKAN METODE MANUAL DESAIN PERKERASAN JALAN 2017 (Studi Kasus Jalan Gor Flobamora-Jalan Kejora, Kota Kupang) - Daru, Fridolin Delawati; Pedo, Krisantus Satrio Wibowo; Manubulu, Christiani Chandra (Eternitas: Jurnal Teknik Sipil, 2024)
The Gor Flobamora-Kejora Road section is one of the alternative routes connecting Oebufu and Tofa District. Damage that occurs on this route is a major factor in disrupting accessibility, comfort and safety. Inconsistencies in planning with construction and use of pavement often cause damage, so an evaluation is needed in determining actions to improve the quality of road service life. This study aims to assess the condition of the road pavement and redesign the pavement. The road condition assessment method uses the 1990 Bina Marga method and the Surface Distress Index (SDI) method, while to redesign the pavement using the 2017 Road Pavement Design Manual Method. The results of the analysis show that the highest SDI value is 115 with minor damage conditions, it is recommended for road rehabilitation, while the Bina Marga method shows the highest Priority Sequence value is 6, with recommendations for periodic maintenance. The dominant type of damage is potholes, with a percentage of damage of 31.56%. The proposed pavement redesign uses flexible pavement with a layer thickness of 4 cm AC WC, 6 cm AC BC, 8 cm AC Base, and 15 cm Class A LPA